Limnologica - Limnologica (Elsevier, 2026)
Limnologica publishes peer-reviewed articles that provide new insights into biological, physical and chemical aspects of freshwater ecosystems and adjacent habitats, both from basic and applied research. We welcome original contributions and reviews to understanding mechanisms that govern ecosystem responses to environmental change (e.g. trophic state, climate, usage, impoundment) or to problem-solving (e.g. ecological engineering, bioindication, restoration and conservation) as well as contributions on aquatic ecosystems or world regions that have been less frequently studied.
FI 0.64
Q2
Keywords: Earth; Space & Environmental Sciences; Environmental Science; Ciencia ambiental; Acuerdos transformativos; Transformative agreements; Ecosistemas de agua dulce; Ingeniería ecológica; Bioindicación; Restauración y conservación